Occurrence of NDM-1, VIM-1, and OXA-10 Co-Producing Providencia rettgeri Clinical Isolate in China - Shen, Siquan; Huang, Xiangning; Shi, Qingyu; Guo, Yan; Yang, Yang; Yin, Dandan; Zhou, Xun; Ding, Li; Han, Renru; Yu, Hua; Hu, Fupin (Frontiers in Cellular and Infection Microbiology, 2022)
Providencia rettgeri is a nosocomial pathogen associated with urinary tract infections related to hospital-acquired Infections. In recent years, P. rettgeri clinical strains producing New Delhi Metallo-β-lactamase (NDM) and other β-lactamase which reduce the efficiency of antimicrobial therapy have been reported. However, there are few reports of P. rettgeri co-producing two Metallo-β-lactamases in one isolate. Here, we first reported a P. rettgeri (P138) strain co-harboring blaNDM-1, blaVIM-1, and blaOXA-10. The species were identified using MALDI-TOF MS. The results of antimicrobial susceptibility testing by broth microdilution method indicated that P. rettgeri P138 was resistant to meropenem (MIC = 64μg/ml), imipenem (MIC = 64μg/ml), and aztreonam (MIC = 32μg/ml). Conjugation experiments revealed that the blaNDM-1-carrying plasmid was transferrable from donor to recipient successfully. The carbapenemase genes were detected using PCR and confirmed by PCR-based sequencing. The complete genomic sequence of the P. rettgeri was identified using Illumina (Illumina, San Diego, CA, USA) short-read sequencing (150bp paired-end reads), and many common resistance genes had been identified, including blaNDM-1, blaVIM-1, blaOXA-10, aac(6')-Il, aadA5, ant(2'')-Ia, aadA1, aac(6')-Ib3, aadA1, aph(3')-Ia, aac(6')-Ib-cr, qnrD1, qnrA1, and catA2. Complete sequence analysis of the plasmid pP138-NDM bearing blaNDM-1 revealed that three other resistance genes were identified in the plasmid, qnrA1, sul1, and ant(2’’)-Ia, conferring resistance to quinolones, sulfonamides, and aminoglycosides, respectively